2008
DOI: 10.1007/s00468-007-0201-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 and nitrogen on wood structure related to water transport in seedlings of two deciduous broad-leaved tree species

Abstract: Wood structure might be altered through the physiological responses to atmospheric carbon dioxide concentration ([CO 2 ]) and nitrogen (N) deposition. We investigated growth, water relations and wood structure of 1-year-old seedlings of two deciduous broad-leaved tree species, Quercus mongolica (oak, a ring-porous species) and Alnus hirsuta (alder, a diffuse-porous species and N 2 -fixer), grown under a factorial combination of two levels of [CO 2 ] (36 and 72 Pa) and nitrogen supply (N; low and high) for 141 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 41 publications
2
20
1
Order By: Relevance
“…However, contradictory results have been published on the effect of elevated CO 2 on wood anatomy. For example, in Q. ilex seedlings (Gartner et al 2003;Watanabe et al 2008) elevated CO 2 in the atmosphere promoted an increase in vessel diameter while no obvious effect was found in other diffuse-porous species such as Populus tremuloides (Kaakinen et al 2004) and Betula pendula (Kostiainen et al 2006). Consistent with the wood anatomical traits in Q. suber seedlings, no differences were found in xylem hydraulic efficiency between CO 2 treatments.…”
Section: Discussionsupporting
confidence: 77%
“…However, contradictory results have been published on the effect of elevated CO 2 on wood anatomy. For example, in Q. ilex seedlings (Gartner et al 2003;Watanabe et al 2008) elevated CO 2 in the atmosphere promoted an increase in vessel diameter while no obvious effect was found in other diffuse-porous species such as Populus tremuloides (Kaakinen et al 2004) and Betula pendula (Kostiainen et al 2006). Consistent with the wood anatomical traits in Q. suber seedlings, no differences were found in xylem hydraulic efficiency between CO 2 treatments.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, it has been illustrated that ambient level of O 3 in Japan was not high enough to suppress the growth of Q. mongolica (Matsumura 2001), but a mathematical model estimated that its annual net production was negatively affected by ambient O 3 in Korea (Wook and Kim 1997). Elevated CO 2 was reported to decrease stomatal conductance and increase water use efficiency but have no significant effect on wood structure in Q. mongolica (Watanabe et al 2008). To date, the combined effects of elevated O 3 and CO 2 on Q. mongolica have not been reported.…”
mentioning
confidence: 96%
“…Many FACE studies showed that eCO 2 did not stimulate vessel size in the stem of several tree species (e.g., Kostiainen et al, 2008, Watanabe et al, 2010. On the other hand, an application of abundant fertilizer rather than eCO 2 stimulated the size of conduit cells (Yazaki et al, 2001;Watanabe et al, 2008). Why no change was found in the lumen size or number of vessels under eCO 2 ?…”
Section: Water Relations and Wood Structurementioning
confidence: 93%
“…In some species there was an increase in the size of the lumen of conduit cells (e.g., Gartner et al, 2003;Kostiainen et al, 2009;, while in others there was not (e.g., Yazaki et al, 2004;Kostiainen et al, 2008;Watanabe et al, 2008).…”
Section: Water Relations and Wood Structurementioning
confidence: 99%
See 1 more Smart Citation